2017
DOI: 10.1080/00071668.2017.1327701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed supplementation with Satureja khuzistanica essential oil on performance and physiological parameters of broilers fed on wheat- or maize-based diets

Abstract: 1. The aim of this study was to evaluate various levels of Satureja khuzistanica essential oil (SKEO) on performance and physiological parameters of broilers fed on wheat- or maize-based diets. 2. Treatments consisted of two cereals (maize- or wheat-based diets) and three levels of SKEO)0, 250 and 500 mg/kg). 3. Feed intake (FI) and body weight gain (BWG) decreased in broilers fed on the wheat-based diets compared to the control diet. Dietary supplementation of 500 mg/kg SKEO increased FI and BWG. Dietary SKEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Also, increased villus height and villus height-to-crypt depth ratio is indicative of increased epithelial cell turnover and a well-differentiated intestinal mucosa, suggesting increased digestive and absorptive capacity ( Fan et al., 1997 ; Jeurissen et al., 2002 ). In agreement with our results, other studies have reported that both essential oil and dietary fibers reduced duodenal crypt depth and increased villus height and villus height-to-crypt depth ratio in the ileum ( Sarikhan et al., 2010 ; Basmacioğlu-Malayoğlu et al., 2016 ; He et al., 2017 ; Masouri et al., 2017 ). Additionally, Giannenas et al.…”
Section: Discussionsupporting
confidence: 93%
“…Also, increased villus height and villus height-to-crypt depth ratio is indicative of increased epithelial cell turnover and a well-differentiated intestinal mucosa, suggesting increased digestive and absorptive capacity ( Fan et al., 1997 ; Jeurissen et al., 2002 ). In agreement with our results, other studies have reported that both essential oil and dietary fibers reduced duodenal crypt depth and increased villus height and villus height-to-crypt depth ratio in the ileum ( Sarikhan et al., 2010 ; Basmacioğlu-Malayoğlu et al., 2016 ; He et al., 2017 ; Masouri et al., 2017 ). Additionally, Giannenas et al.…”
Section: Discussionsupporting
confidence: 93%
“…The wide range of bioactive properties of Satureja EOs makes them appealing to several applications such as: i) flavor agents in the food processing and cosmetic industry (Lerebour et al, 2016(Lerebour et al, , 2014Oliveira et al, 2011); ii) replacers of synthetic insecticides, fungicides, bactericides and nematicides for plant protection and against household pests (Chantraine et al, 1998;Kotan et al, 2010;Maedeh et al, 2011;Picard et al, 2012;Sarkhosh et al, 2018;Tozlu et al, 2011), iii) disinfection agents of microbial-contaminated industrial surfaces (Chorianopoulos et al, 2008;Lebert et al, 2007), iv) antibiofilm agents in dentifrice or mouthwashes formulations (Gursoy et al, 2009), v) natural preservative ingredients in food products (Alexa et al, 2018;Hashemi et al, 2012;Oliveira et al, 2011;Ozkan et al, 2007), vi) additives in films and coatings for active food packaging (Atarés and Chiralt, 2016;Choulitoudi et al, 2016;Kfoury et al, 2015;Nasiri et al, 2018), and vii) feed ingredients, since these EOs have recognized phytobiotic effects by reducing plasma cholesterol and triglycerides concentration and the levels of pathogenic bacteria, enhancing the immune status when used in poultry diets (Hashemipour and Kermanshahi, 2013;Masouri et al, 2017;Sadeghi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed an increase in lactic acid bacteria and a decrease in coliform counts by the assessed feed additives. Masouri et al (2017) and Mahgoub et al (2019) observed similar results on lactic acid bacteria and on E. coli or coliform counts using Satureja khuzistanica essential oil and ROE in chickens and quail, respectively. However, some studies have shown no influence of EOs on lactic acid bacteria (Mohiti‐Asli & Ghanaatparast‐Rashti, 2018) or on both coliform and lactic acid bacteria (Kırkpınar et al, 2011).…”
Section: Discussionmentioning
confidence: 57%